Jayatu Keśava, jayatu Mādhava : ʻDivya vāṇī keśavācī āṇi ʻYajñarūpa jīvana jyāñce yā dona racanāñce sãyukta saṅkalana - Pullīvāra, Mukunda (Rāshṭrabhāvanā Prakāśana, 1981)
Two verse works on the lives and works of Keshav Baliram Hedgewar, 1889-1940 and Madhav Sadashiv Golwalkar, leaders of the Rashtriya Swayamsevak Sangh, Hindu militant organization.